1989
DOI: 10.1143/jjap.28.l2196
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the 2223 Phase in Leaded Bi-Sr-Ca-Cu Oxide under Reduced Oxygen Partial Pressure

Abstract: The growth process of 2223 phase in a leaded Bi-Sr-Ca-Cu oxide system has been investigated under various oxygen partial pressures using differential thermal analysis, combined with XRD of the quenched specimen. It is shown that under a slow heating rate, the DTA curves exhibit two or three endothermic peaks between 820 to 900°C, and the peak positions are lowered with reduction in the O2 partial pressure. The 2223 phase is found to grow most efficiently in the partial melting state sandwiched between the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…It is known that the calcined precursor powders used for the synthesis of the Bi, Pb(2223) phase undergo an endothermic reaction at T ≈ 855 • C (in air), which is easily detectable in DTA traces [5][6][7] (peak A in Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the calcined precursor powders used for the synthesis of the Bi, Pb(2223) phase undergo an endothermic reaction at T ≈ 855 • C (in air), which is easily detectable in DTA traces [5][6][7] (peak A in Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The SEM studies revealed that the powder was in the form of a plate with a thickness of about 0.5 //m. 9 These analyses confirmed that the powder consisted almost entirely of the 110 K phase. Figure 2 shows the temperature dependence of magnetization for the powder.…”
Section: A Characterization Of the Powder Used For The Screen Printingmentioning
confidence: 72%
“…The large endothermic peak in both powders was attributed to the melting of the Bi2212 phase. 25 As indicated by the XRD results ( Fig. 1), the main difference between powders I and II was the Ca 2 PbO 4 content, i.e., a large amount of Ca 2 PbO 4 present in the former and little in the latter.…”
Section: (3) Melting Behaviormentioning
confidence: 84%
“…[11][12][13][14] It is believed that Pb substitution improves reaction kinetics via formation of a Ca 2 PbO 4 -related liquid phase. [15][16][17] However, excessive liquid results in the formation of large nonsuperconducting phases and causes deterioration of current-carrying capacity of the tapes. 18,19 To avoid the formation of excessive liquid, a relatively low sintering temperature has to be used in the Pb-substituted Bi2223 system; because of the low sintering temperature, Bi2223 phase formation is sluggish and the required sintering time is long.…”
Section: Introductionmentioning
confidence: 99%